Perancangan Aplikasi Pengarsipan (E-Archive) Dokumen Kepegawaian Pada Universitas Advent Indonesia - Govin Sony; Yulianus Palopak (TeIKa, 2018)
Current technological developments are developing very rapidly. All of that aims to provide convenience for technology users in carrying out their work. Document archives are currently still managed in a conventional manner. The purpose of this study is to help employee document archiving to be more systematic, structured, to simplify the process of finding employee document archives. The method in this study uses SDLC and by conducting interviews. The conclusion of this study is that employee document archiving applications assist in terms of digital document storage so that data becomes computerized and not easily damaged, employee document archiving applications facilitate in terms of searching employee document data, so that the employee document search process can be done more easily and quickly, Document archiving applications can already share data and the download process is done properly and correctly, the application already has access rights to each user so that the system can share data in accordance with user access rights. The suggestions from this study are expected that this application can be made in the form of mobile-based on Android and iOS so that this application can be more easily accessed, it is hoped that this application can be made into a staffing application so that its use is more complete and easier for future users.